2011
DOI: 10.1021/jp109665a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Uranyl Nitrate Ion Pairs Complexed with Amide Ligands Using Electrospray Ionization Ion Trap Mass Spectrometry and Density Functional Theory

Abstract: Ion populations formed from electrospray of uranyl nitrate solutions containing different amides vary depending on ligand nucleophilicity and steric crowding at the metal center. The most abundant species were ion pair complexes having the general formula [UO(2)(NO(3))(amide)(n=2,3)](+); however, singly charged complexes containing the amide conjugate base and reduced uranyl UO(2)(+) were also formed as were several doubly charged species. The formamide experiment produced the greatest diversity of species res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…However, most other gas-phase experiments produce only singly charged uranium species. Recent spectroscopy experiments have isolated uranium and its oxides in rare gas matrixes or in the gas phase to probe the structure and bonding in these systems, and computational studies have complemented this work. Selected complexes of uranium or its oxide ions have been investigated with mass spectrometry to explore solvation and coordination. In the present work, we investigate mass-selected uranium oxide ions with infrared spectroscopy in the oxide stretching region.…”
mentioning
confidence: 99%
“…However, most other gas-phase experiments produce only singly charged uranium species. Recent spectroscopy experiments have isolated uranium and its oxides in rare gas matrixes or in the gas phase to probe the structure and bonding in these systems, and computational studies have complemented this work. Selected complexes of uranium or its oxide ions have been investigated with mass spectrometry to explore solvation and coordination. In the present work, we investigate mass-selected uranium oxide ions with infrared spectroscopy in the oxide stretching region.…”
mentioning
confidence: 99%
“…instrumental flexibility and variety of ionization techniques; including wide dynamic temperature regime; fast for operation and stage limited sample preparation steps, encompassing analysis in solutions, semi-liquid and solid state, makes mass spectrometry a method of choice for uranium speciation (Pajo et al 2001;Steppert et al 2012;Crawford et al 2012;Rutkowski et al 2011;Gresham et al 2011;Jennings et al 1989). Its applicability involves complex multicomponent homogeneous and heterogeneous environmental samples, including stages of the nuclear fuel cycle such as treatment of liquid wastes and/or dried fuel storage, where the assessment of uranium oxides reactivity [ 100-250°C is of considerable interest (He et al 2010;Lotnik et al 2001;Yusov and Shilov 2007;Kulyukhin and Kamenskaya 2010;Nagaishi et al 1998;Gorshkov et al 2001;Rios et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This technique is known to be used in combination with traditional solution chemistry techniques to investigate metal–ligand interactions. , Actinide species have been studied by ESI-MS since the early 1990s where the use of electrospray mass spectrometry was utilized for the analysis of various elements including U­(VI), , Th­(IV), Am­(III), , Np and Pu in different oxidation states. The publications range from species identification to specific interest in the chemistry of the f-elements ,, through the investigation of competitive interactions . Additionally, a number of studies have included the use of ESI-MS to investigate the gas phase behavior of UO 2 + , UO 2 2+ , PuO 2 + and PuO 2 2+ ,, , Pu­(III), ,, Pu­(IV) gas phase behavior , and Rios et al reported the gas phase reduction of PuO 2 2+ to Pu­(V) and Pu­(IV) followed by ESI-MS . The ESI-MS spectra in positive ionization mode of 1 after dissolution of some crystals in THF and 1/1000 dilution in CH 3 CN are reported in the Figures S5 and S6.…”
Section: Resultsmentioning
confidence: 99%